Fabrikasi Transparant Conducting Film Berbahan Dasar Grafit pada Substrat Plastik dengan Proses Mekanik - Rahman, Dui Yanto; Sustini, Euis; Abdullah, Mikrajuddin (Institut Teknologi Bandung, 2017)
Transparent Conducting Film (TCF) employing graphite powder as conducting material has been successfully fabricated by using extremely cheap and simple method.  This method doesn’t use heating and transfer process which is commonly used in fabrication of Transparent Conducting Film. Graphite powder was directly deposited on the surface of plastic using circle motion of tube shaped-metal which its surface was covered with thick tissue. The film thickness was varied to investigate the influence of it to the transmittance and resistance of the film. The transmittance and resistance measurement was carried out under UV-Vis electrometer and I-V El-Kahfi equipment assistance, and finally the transmittance of 60% and resistance of 24,4 kΩ was gained for one time of coating, While 9 times of coating produced 13% of transmittance and 773 Ω of resistance.